Antimicrobial resistance and biological governance: explanations for policy failure. Issue 10 (October 2015) - Wallinga, D.; Rayner, G.; Lang, T.
Abstract: The paper reviews the state of policy on antimicrobial use and the growth of antimicrobial resistance (AMR). AMR was anticipated at the time of the first use of antibiotics by their originators. For decades, reports and scientific papers have expressed concern about AMR at global and national policy levels, yet the problem, first exposed a half-century ago, worsened. The paper considers the explanations for this policy failure and the state of arguments about ways forward. These include: a deficit of economic incentivisation; complex interventions in behavioural dynamics; joint and separate shifts in medical and animal health regimes; consumerism; belief in technology; and a narrative that in a 'war on bugs' nature can be beaten by human ingenuity. The paper suggests that these narratives underplay the biological realities of the human-animal-biosphere being in constant flux, an understanding which requires an ecological public health analysis of AMR policy development and failure. The paper suggests that effective policy change requires simultaneous actions across policy levels. No single solution is possible, since AMR is the result of long-term human intervention which has accelerated certain trends in the evolution of a microbial ecosystem shared by humans, animals and other biological organisms inhabiting that ecosystem. Viewing the AMR crisis today through an ecological public health lens has the advantage of reuniting the social-ecological and bio-ecological perspectives which have been separated within public health.